The Effectiveness of Game Quizizz Using Learning Media On Students' Outcomes : The Effectiveness of Game Quizizz Using Learning Media On Students' Outcomes - Almanna Wassalwa; Ukhtul Iffah (JOEY: Journal of English Ibrahimy, 2022)
In this neo culture technology, the role of technology and media, then becomes very large in the 21st century learning process and its various implications. In learning process may vary between teachers, technology, and media. This study aims to determine the influence of Quizizz learning material-based educational games on the performance of junior high school students in foreign language dormitories at Language Boarding House (LBH) Salafiyah Syafi’iyah Sukorejo. This research used a non-equivalent group, a post-trial semi-experimental research design, it is an examination of learning activities in the form of actions that deliberately appeared and occur in the class simultaneously. Collection of the data techniques were done by tests and questionnaire. The use of Quizizz educational game-based learning materials is effective in improving the academic achievement of Intermediate Foreign Language Boarding (LBH) students. It is proven by the t count’s value (3.373) > t table (2.160). The results of the effective use of Quizizz educational game-based learning media are high/good on the learning outcomes of Intermediate Language Boarding House (LBH) students. It is indicated by the percentage of students with scores greater than or equal to 80 is 43% percent and the percentage of students with scores greater than or equal or equal to 70 is 86%. And the percentage of student response questionnaires shows that 71% of student responses are very good and 29% are good.